Review: In vitro study revealed sugar as anticancer constituent = İn vitro Çalışmalar Şekeri Bir Antikanser Bileşeni Olarak Gösteriyor; Literatür Derleme - Md Isa, Muhammad Lokman; Ramli, Nuramalina; Ismail, Isma Syahril; Shahbuddin, Munira; Mat Yusof, Afzan; Ramli, Roszaman (Dergi Park Akademik, 2017)
The majority of deaths among cancer patients are attributed to the metastatic spread of cancer cells to vital organs instead of primary tumor outgrowth. Plus, cancer therapeutics which focusing on conventional chemotherapy is often toxic not only to tumor cells but also to normal cells and caused their therapeutic use is limited. In this review, aberrant glycosylation is proposed to be a method of cancer diagnosis in order to identify cancer at its earliest and more treatable stage. Aberrant glycosylation is a universal feature of cancer cells. Glycosylation, the attachment of sugar moieties to protein, is a major form of post-translational modifi cation (PTM) that is observed in approximately half of all proteins. Certain glycan structures are well known markers for tumor progression and its availability and composition in the microenvironment may affect glycosylation of the cell. In order to understand the biological application of simple sugars as anticancer agents, it is vital to fundamentally investigate the relationship between simple sugars and cell proliferation using living cell lines in vitro. Various simple sugars have been studied previously in a number of cancer cell lines representing different evolutionary stages of cancer. It has been examined that there is a selective effect of individual simple sugars on the pattern of growth and metabolism of certain cell lines in tissue culture. The results from previous studies reported that certain simple sugars were able to alter the growth pattern and morphology of several cancer cell lines which indicate that sugars have antiproliferative effect on cancer cells.